A handbook of training and development - Ramaswami, N. (Madra, India : T.R. Publications, 1992)
This handbook has described the various aspects of training and development, including motivation, communication, communication, the modes and methods and problems and solution of training.
Includes bibliographical references and index.
aia 11/08/2016; rpm 21/02/2018
Loans
Keywords: Employees; Training & development